An Analysis of Illocutionary Acts Used in The Speech of Ridwan Kamil as Jakarta Governor Candidate - Sri, Wiwi Widuri Sinta Putri; Septiana, Ponia Mega; Yuliyanti, Ai Yeni; Sari, Titania (Social and Economic Bulletin, 2025)
This research analyzes the illocutionary acts present in Ridwan Kamil's campaign speeches for the 2024 Jakarta gubernatorial election. It shows how political speeches change perspectives, audiences, and candidates. Kamil engages diverse voters with his funny, sympathetic, and aggressive communication. This study classifies Kamil's illocutionary acts—assertive, commissive, directive, and expressive—using speech act theory to uncover his political appeal's vocabulary. Voter trust requires 25 assertive actions to develop credibility and 12 commissive acts to express future governance. Directive activities (5), which gain audience support, and expressive acts (2), which provoke emotion, were rarer, showing a tactical concentration on substantive substance. Kamil's remarks match people's expectations for sensible, solution-oriented leadership with clarity and tangible guarantees, according to research. This extensive examination of how language might strategically influence voter behavior and understanding enriches political communication literature. The study proposes future research into cross-cultural comparisons and political speech expression, particularly in different electoral circumstances. Kamil appealed to Jakarta's voters by tailoring his message to diverse audiences in formal and informal settings.